Riot - Myers, Walter Dean (Egmont USA, 2009)
In 1863, fifteen-year-old Claire, the daughter of an Irish mother and an African father, faces ugly truths and great danger when Irish immigrants, enraged by the Civil War and a federal draft, lash out against African-Americans and wealthy "swells" of New York City.